THE CONTENT OF THE NEW DRAFT CONSTITUTION OF THE NEW UZBEKISTAN - Hakimova Nilufar Takhirjonovna; Khakimov Ulugbek Takhirjan ugli (Scholar Express Journals, 2023)
The main additions and changes of the draft of the New Constitution of New Uzbekistan are the most important news. and it is stated that the principles of "State for Man" are the basis of the solid legal basis of democratic processes
Keywords: Development strategy of New Uzbekistan; New Uzbekistan; State for man